2005
DOI: 10.1111/j.0022-202x.2005.23859.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of a Peptide Inhibitor of Transforming Growth Factor-β1 Ameliorates Bleomycin-Induced Skin Fibrosis

Abstract: Transforming growth factor-beta (TGF-beta) plays a crucial role in the pathogenesis of skin fibrotic diseases. Systemic TGF-beta inhibitors effectively inhibit fibrosis in different animal models; however, systemic inhibition of TGF-beta raises important safety issues because of the pleiotropic physiological effects of this factor. In this study, we have investigated whether topical application of P144 (a peptide inhibitor of TGF-beta1) ameliorates skin fibrosis in a well-characterized model of human scleroder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
102
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 154 publications
(110 citation statements)
references
References 36 publications
3
102
0
4
Order By: Relevance
“…There is a large body of indirect evidence implicating the overexpression of TGF␤ ligand or receptor in the pathogenesis of SSc (23), and several recent studies have demonstrated that blocking TGF␤ ligand may abrogate fibrosis in a number of mouse models (24). In addition, activation of TGF␤ signaling pathways constitutively in fibroblasts replicates many of the key histologic and biochemical features of established SSc (25).…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of indirect evidence implicating the overexpression of TGF␤ ligand or receptor in the pathogenesis of SSc (23), and several recent studies have demonstrated that blocking TGF␤ ligand may abrogate fibrosis in a number of mouse models (24). In addition, activation of TGF␤ signaling pathways constitutively in fibroblasts replicates many of the key histologic and biochemical features of established SSc (25).…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45] We show that intraperitoneal administration of these blocking peptides to mice exposed to PD fluid preserved the peritoneal morphology and function and decreased the accumulation of different subpopulations of "fibroblast-specific protein-1" (FSP-1) fibroblasts, especially of those co-expressing the mesothelial marker cytokeratin. These cells with intermediate phenotype (Cyto ϩ /FSP-1 ϩ ) displayed myofibroblastlike characteristics including fibrogenic capacity.…”
mentioning
confidence: 90%
“…This dose of P17 was similar to that used in previous studies. [42][43][44][45] For quantitative RT-PCR analysis, mesothelial cells were lysed in TRI reagent (Ambion, Inc., Austin, TX), and RNA was extracted as per fabricant instructions. Complementary DNA was synthesized from 2 g of total RNA by reverse transcription (RNA PCR Core Kit, Applied Biosystems, Inc.).…”
Section: Culture Of Mesothelial Cells and Treatmentsmentioning
confidence: 99%
“…Both cytokines are up-regulated in the skin of SSc patients and strongly stimulate matrix synthesis by dermal fibroblasts. Accordingly, blockade of TGF␤ or PDGF signaling has been shown to reduce the development of fibrosis in various experimental models (6)(7)(8)(9). However, substances that specifically inhibit PDGF pathways are not yet available for clinical application.…”
mentioning
confidence: 99%